Semiconductor water-based inks: Miniaturized NiO pseudocapacitor electrodes by inkjet printing. Issue 9 (August 2019) - Yus, J.; Gonzalez, Z.; Sanchez-Herencia, A.J.; Sangiorgi, A.; Sangiorgi, N.; Gardini, D.; Sanson, A.; Galassi, C.; Caballero, A.; Morales, J.; Ferrari, B.
Abstract: The formulation, development and optimization of water-based inks of platelet-like nanoparticles are the main objective of this work. As-synthesized Ni(OH)2 nanoparticles were dispersed and stabilized in aqueous suspension by PEI addition. The combination of DEG (cosolvent) with H2 O shows the ideal values of surface tension and viscosity for piezoelectric inkjet printing, which exhibits a homogeneous jetting flow of the nanoplatelets suspension. The printed nanostructure was sintered at low temperature (325 °C) and the electrochemical overview of NiO electrode behavior was described. These printable pseudocapacitors tested by a three-electrode cell have showed a competitive specific capacitance, leading 92% and 78% of capacitance retention for 2000 cycles at scan rates of 1 and 2 A/g respectively, and a coulombic efficiency of 100%. The initial performance of this printed NiO pseudocapacitor can be compared with others prepared by conventional methods. This new finding is expected to be particularly useful for the designing of micro-pseudocapacitors.